Conserved architecture of brain transcriptome changes between Alzheimer's disease and progressive supranuclear palsy in pathologically affected and unaffected regions. (December 2021) - Wang, Xue; Allen, Mariet; Reddy, Joseph S.; Carrasquillo, Minerva M.; Asmann, Yan W.; Funk, Cory C; Nguyen, Thuy; Malphrus, Kimberly G.; Younkin, Steven G.; Dickson, Dennis W; Price, Nathan D; Golde, Todd E; et al.
Abstract: Background: Alzheimer's disease (AD) is a complex proteinopathy with abnormal accumulation of amyloid β and tau in which the temporal cortex (TCx) is severely affected. Progressive supranuclear palsy (PSP) is a primary tau proteinopathy. Neurodegeneration in the TCx is less severe in PSP than in AD. In contrast, the cerebellum (CER) is relatively spared from gross pathology especially in AD. To determine if there are shared molecular changes that occur in both AD and PSP and explore these in the context of neuropathological burden, we analyzed RNAseq data from post‐mortem TCx and CER of AD and PSP patients, as well as controls without neurodegenerative disease. Method: For each brain region, we performed differential gene expression analyses between AD and normal controls (ADvC), and between PSP and controls (PSPvC) using two linear regression models independently. The first model adjusted for sex, age, and technical variables, whereas the second model adjusted for cellular composition in addition to the variables included in the first. We performed comparative analysis (Pearson correlation) of the results between disease groups and brain regions. Result: The slope and Pearson correlation between β coefficients of DEGs obtained from PSPvC and those from ADvC were highly significant for both TCx (slope=0.31, R 2 =0.27, p<1.0E‐10) and CER (slope=0.78, R 2 =0.69, p<1.0E‐10). The slope and correlation between the β coefficients increased with increasing significance of DEGs, approaching R 2 =1 for DEGs with q<0.01. These observations held for both models. Comparison of β coefficients between TCx ADvC and CER ADvC, and between TCx PSPvC and CER PSPvC revealed similar trends. Enrichment analysis identified shared pathways implicated in both diseases. Conclusion: There is a striking correlation in the directionality and magnitude of significant gene expression changes in brain transcriptomes between AD and PSP and between the temporal and cerebellar cortices. These findings indicate conservation in transcriptomic alterations due to common proteinopathies or their downstream effects and demonstrate the widespread perturbations of systems in the whole brain in neurodegenerative diseases. This work highlights the presence of transcriptome changes in pathologically "unaffected" brain regions and identifies biological pathways that are ubiquitously altered across brain regions and distinct neurodegenerative diseases.